Why the Current Tax Rate Tells You Little: Competing for Mobile and Immobile Firms - Dominika Langenmayr; Martin Simmler (Center for Economic Studies and ifo Institute (CESifo), 2017)
Firms should use all available information to anticipate future tax rates. Firm mobility, as a key determinant of corporate tax rates, is one such source of information. We first show theoretically that a government sets a higher tax rates on firm profits if average firm mobility in its jurisdiction is low, and that the potential entry of immobile firms in the future deters firms from entering a jurisdiction today. We then test and confirm these predictions in a well-identified setting, using the rapid growth of wind power plants (a very immobile industry) and the large variation in local business taxes across Germany for identification.
Keywords: H25; H71; F21; 330; corporate taxation; firm mobility; commitment; tax competition